2013
DOI: 10.1007/s00213-013-2992-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of cortisol and psychopathy in the cycle of violence

Abstract: Rationale Child abuse and neglect are universal risk factors for delinquency, violence, and aggression; this phenomenon is known as the cycle of violence. Additional factors—psychopathy, impulsiveness, and disruptions in the hypothalamic–pituitary–adrenal (HPA) axis—play a role in aggressive behavior but have rarely been examined in the same conceptual and experimental framework. Objectives We sought to examine the above-mentioned risk factors for aggression in a prospective study employing psychopharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 54 publications
2
24
0
1
Order By: Relevance
“…A number of such studies have been identified in the literature, and many have found executive impairments in adults of various ages who were exposed to some form of childhood maltreatment (Brandes et al, 2002;Navalta et al, 2006;Stein et al, 2002;Twamley et al, 2004). Functional neuroimaging studies of adult victims of childhood maltreatment have also identified alterations in the neuroendocrine system (HPA axis), which influence cognitive processes such as language, memory, and executive functions (Carpenter, Shattuck, Tyrka, Gerac-ioti, & Price 2011;Gowin et al, 2013;Mezzacappa et al, 2001). These individuals may also display impaired prefrontal cortex development (Glaser, 2000;Van der Kolk, 2003) and neurological maturation, disrupting neuronal growth and plasticity (Lee & Hoaken, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of such studies have been identified in the literature, and many have found executive impairments in adults of various ages who were exposed to some form of childhood maltreatment (Brandes et al, 2002;Navalta et al, 2006;Stein et al, 2002;Twamley et al, 2004). Functional neuroimaging studies of adult victims of childhood maltreatment have also identified alterations in the neuroendocrine system (HPA axis), which influence cognitive processes such as language, memory, and executive functions (Carpenter, Shattuck, Tyrka, Gerac-ioti, & Price 2011;Gowin et al, 2013;Mezzacappa et al, 2001). These individuals may also display impaired prefrontal cortex development (Glaser, 2000;Van der Kolk, 2003) and neurological maturation, disrupting neuronal growth and plasticity (Lee & Hoaken, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors (Grassi-Oliveira et al, 2008;Hart & Rubia, 2012;Jaffee & Maikovich-Fong, 2011;Tanakaa, Wekerleb, Schmuckc, & Paglia-Boakd 2011), childhood maltreatment can affect the development of brain structures such as the corpus callosum, the left neocortex, the hippocampus, and the amygdala. Exposure to maltreatment can also cause neurofunctional and neurohumoral alterations, increasing the excitability of limbic structures, and 'reprogramming' the hypothalamic-pituitary-adrenal (HPA) axis, leading to disturbances in the stress response (Frodl & O'Keane, 2013;Gowin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…On average, the aggressive men’s physiological responses were consistent with the idea that their sexual aggression was more strongly associated with hyporeactivity than with hyperreactivity. Although there are a few exceptions, (e.g., Feilhauer et al, 2013; Gowen et al, 2013 ), cortisol and EDA hyporeactivity have been found in an abundance of studies to be related to psychopathy and antisocial behaviors (e.g., Holi et al, 2006; Loney et al, 2006; Lorber, 2005; O’Leary et al, 2007). In contrast, physiological hyperreactivity has been found to be related to negative affectivity, including trait levels of depression, anxiety, anger, and hostility (e.g., Kreibig, 2010; Pope & Smith, 1991; Steptoe et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This does not mean, of course, that Behavior Analysis has been neglecting the general topic of aggressive behavior as a relevant subject. Actually, recent contributions of Behavior Analysis to the understanding of certain aspects of aggressive behavior can be found in applied research areas as problem behavior (e.g., Beavers, Iwata, & Lerman, 2013), and in basic psychopharmacological research, as a reliable laboratory test of human aggressive behavior (e.g., Gowin, Green, Alcorn, Swann, Moeller, & Lane, 2013). It is noteworthy that late behavior-analytic research on aggression focus on human subjects, while the surveyed studies showed a tendency to employ nonhuman subjects (cf.…”
Section: Concluding Commentsmentioning
confidence: 99%